Evolution or Degradation? Philosophical Underpinnings for Exploring the Future of Humanity in David Cronenberg’s Crimes of the Future / ¿Evolución o degradación? Fundamentos filosóficos para explorar el futuro de la humanidad en “Crímenes del futuro” de David Cronenberg / Эволюция или деградация? Философские основания исследования будущего человечества в «Преступлениях будущего» Дэвида Кроненберга - OLEG N. GUROV / ГУРОВ О.Н. (Наука телевидения)
The paper presents an analysis of David Cronenberg’s 2022 film Crimes of the Future, dedicated to the transformation of human nature amidst technological progress. Drawing inspiration from leading contemporary thinkers like Gilles Deleuze, Felix Guattari, Maurice Merleau- Ponty, Michel Foucault, Donna Haraway, and Timothy Morton, the research extends to Cronenberg’s other films to provide a deeper comprehension of his creative vision. Central to the discussion are the humanitarian issues posed by these movies, namely the metamorphosis of human corporeality, the blurring boundaries between the natural and artificial, and the ethical dilemmas arising from biotechnological interventions in human physiology. The key themes in Crimes of the Future are contextualized within modern frameworks of dark ecology and posthumanism and interpreted through the lens of Deleuze and Guattari’s body without organs, Merleau-Ponty’s phenomenology, and Foucault’s biopolitics. Crimes of the Future offers a multifaceted reflection on humanity’s future amidst profound transformations of both physiology and environment. Through an in-depth analysis of the film and Cronenberg’s oeuvre at large, new topics emerge for interdisciplinary research at the intersection of philosophy, bioethics, sociology, and psychology, exploring how human nature and identity evolve in an era of dynamic technological advancement.